2014
DOI: 10.1111/jopr.12150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Implant/Abutment Connection on Stress Distribution to Implant‐Surrounding Bone: A Finite Element Analysis

Abstract: There was a difference in the stress location on the prosthetic components of the systems studied; however, it did not influence trabecular bone stress generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
2
8
0
1
Order By: Relevance
“…Our findings are consistent with a number of studies that have demonstrated the advantages of Morse-tapered internal connections compared to the traditional butt joint connection (Tesmer et al 2009;Aloise et al 2010;Tripodi et al 2012;Raoofi et al 2013). Recent studies have demonstrated that the Morse taper internal connection, with conical interference seal, provides strong resistance to applied eccentric forces and bending moments and provides improved mechanical stability to the abutment connection (Ugurel et al 2013;Hanaoka et al 2014;Schmitt et al 2014). The rigid connection and the friction between the implant and the abutment results in reduced micromovements between the two parts and thus prevents the resorption of the crestal bone (King et al 2002).…”
Section: The Effect Of Type Of Fixture/abutment Connection On Peri-immentioning
confidence: 99%
“…Our findings are consistent with a number of studies that have demonstrated the advantages of Morse-tapered internal connections compared to the traditional butt joint connection (Tesmer et al 2009;Aloise et al 2010;Tripodi et al 2012;Raoofi et al 2013). Recent studies have demonstrated that the Morse taper internal connection, with conical interference seal, provides strong resistance to applied eccentric forces and bending moments and provides improved mechanical stability to the abutment connection (Ugurel et al 2013;Hanaoka et al 2014;Schmitt et al 2014). The rigid connection and the friction between the implant and the abutment results in reduced micromovements between the two parts and thus prevents the resorption of the crestal bone (King et al 2002).…”
Section: The Effect Of Type Of Fixture/abutment Connection On Peri-immentioning
confidence: 99%
“…Moreover, the Morse taper connection have greater resistance to torque loss than other connection models [16]. This system seems to have less tension on the abutment screw, the cone compensates for the high stresses and protects the screw from overload [17].…”
Section: Introductionmentioning
confidence: 99%
“…The material properties employed are detailed in Table 1 [8]. A complete osseointegration was added to both the trabecular and the cortical bone with the implant [9]. The models were subjected to an axial load of 100 N distributed throughout the region on the cantilever from the distal implant with reference to the midline and to a 30 N axial load on the implants in the inter-foramen region, both in model 1 and in model 2, as shown in Figure 3 [10,11].…”
Section: Methodsmentioning
confidence: 99%